Circ‐MALAT1 Functions as Both an mRNA Translation Brake and a microRNA Sponge to Promote Self‐Renewal of Hepatocellular Cancer Stem Cells. Issue 4 (21st December 2019) - Chen, Liang; Kong, Ruijiao; Wu, Cong; Wang, Shuo; Liu, Zixin; Liu, Shupeng; Li, Shuiping; Chen, Tian; Mao, Chuanbin; Liu, Shanrong
Abstract: Both circular RNAs (circRNAs) and cancer stem cells (CSCs) are separately known to be involved in cancer, but their interaction remains unclear. Here, the regulation of hepatocellular CSC self‐renewal is discovered by a circRNA, circ‐MALAT1, which is produced by back‐splicing of a long noncoding RNA, MALAT1. Circ‐MALAT1 is highly expressed in CSCs from clinical hepatocellular carcinoma samples under the mediation of an RNA‐binding protein, AUF1. Surprisingly, circMALAT1 functions as a brake in ribosomes to retard PAX5 mRNA translation and promote CSCs' self‐renewal by forming an unprecedented ternary complex with both ribosomes and mRNA. The discovered braking mechanism of a circRNA, termed mRNA braking, along with its more traditional role of miRNA sponging, uncovers a dual‐faceted pattern of circRNA‐mediated post‐transcriptional regulation for maintaining a specific cell state. Abstract : Self‐renewal of hepatocellular cancer stem cells (CSCs) is found to be regulated by a circRNA, circ‐MALAT1, through a new mechanism termed mRNA braking. Circ‐MALAT1 functions as a brake in ribosomes to retard PAX5 mRNA translation and promote CSCs' self‐renewal by forming an unprecedented ternary complex with both ribosomes and mRNA.